CHIP-dependent regulation of the actin cytoskeleton is linked to neuronal cell membrane integrity - Dias, Catarina; Nita, Erisa; Faktor, Jakub; Tynan, Ailish C; Hernychova, Lenka; Vojtesek, Borivoj; Nylandsted, Jesper; Hupp, Ted R; Kunath, Tilo; Ball, Kathryn L (iScience, 2021)
CHIP is an E3-ubiquitin ligase that contributes to healthy aging and has been characterized as neuroprotective. To elucidate dominant CHIP-dependent changes in protein steady-state levels in a patient-derived human neuronal model, CHIP function was ablated using gene-editing and an unbiased proteomic analysis conducted to compare knock-out and wild-type isogenic induced pluripotent stem cell (iPSC)-derived cortical neurons. Rather than a broad effect on protein homeostasis, loss of CHIP function impacted on a focused cohort of proteins from actin cytoskeleton signaling and membrane integrity networks. In support of the proteomics, CHIP knockout cells had enhanced sensitivity to induced membrane damage. We conclude that the major readout of CHIP function in cortical neurons derived from iPSC of a patient with elevate α-synuclein, Parkinson's disease and dementia, is the modulation of substrates involved in maintaining cellular "health". Thus, regulation of the actin cytoskeletal and membrane integrity likely contributes to the neuroprotective function(s) of CHIP.
Keywords: proteomics; cell biology; omics; organizational aspects of cell biology; bioinformatics